Microtus xanthognathus Leach 1815 ... - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Microtus xanthognathus Leach 1815 Microtus xanthognathus Leach 1815, Zool. Misc., Vol. 1: 60. Type Locality: Canada, Manitoba, Hudson Bay. Vernacular Names: Taiga Vole. Distribution: Western boreal taiga zone, from EC Alaska to W Northwest Territories, southeastwards to C Alberta and W coast of Hudson Bay, Canada. Conservation: IUCN – Lower Risk (lc). Discussion: Relationships obscure—apparently not a sister species to M. chrotorrhinus as once believed (see that account and Lidicker and Yang, 1986) nor closely related to M. richardsoni, subgenus Aulacomys, as arranged by Zagorodnyuk (1990; see Conroy and Cook, 2000 a). Karyotype reported and affinities discussed by Rausch and Rausch (1974). Late Pleistocene distribution reached C and E USA, as far south as S Nebraska, N Arkansas, and Virginia (Graham and Lundelius, 1994). ... : Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Cricetidae, pp. 955-1189 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins University Press on page 1019, DOI: 10.5281/zenodo.7316535 ...